Bubble Mobilization Pressure in a Small‐Diameter Tube. Issue 11 (2nd October 2015) - Uchiyama, Hiroki; Kariyasaki, Akira; Kagawa, Masazumi; Yamasaki, Yoshikazu; Matsukuma, Yosuke; Morooka, Shigeharu
Abstract: The mobilization pressure was measured for a train of bubbles in a capillary tube when the liquid film forming between the bubble surface and the inner surface of the duct does (Case B) and does not cover the bubble surface (Case A). In Case A, the measured bubble mobilization pressure mostly agreed with the estimated capillary pressure for different numbers of bubbles in the duct. In Case B, the bubble mobilization pressure was lower, with a larger scatter than in Case A. Increasing the number of bubbles caused the mobilization pressure to converge to the Case B results. Factors that affect the mobilization pressure were considered. Abstract : The dependence of the bubble mobilization pressure in a capillary tube on various factors was experimentally determined for the two cases when the liquid film forming between the bubble surface and the inner surface of the duct covers or does not cover the bubble surface. The mechanism for the motion of the liquid film surrounding the bubbles was evaluated for visualization.